English textbook evaluation: a Saudi EFL teacher’s perspective - Alshumaimeri, Yousif; Alharbi, Turki (Frontiers in Education, 2024)
IntroductionTextbook evaluation plays a crucial role in enhancing language education by ensuring instructional materials meet learners’ needs. Hence, this study examines the “Mega Goal” textbook series used in English as a Foreign Language (EFL) education through the evaluation of 773 male EFL teachers selected from Saudi Arabia’s secondary schools.MethodsA quantitative approach was adopted using a descriptive survey. A structured questionnaire collected via Google Forms was employed to obtain the teachers’ assessment of the series. The resultant data were systematically analyzed employing descriptive statistics to present the teachers’ perspectives across multiple domains. The dataset explored practical factors, language content, layout and structure, language abilities, tasks and exercises, and cultural elements. Techniques like Kruskal-Wallis tests were also used to examine differences in evaluations according to teachers’ qualifications, experience, and region.ResultsFindings indicated that the series’ external aspects such as structure and arrangement garnered positive reviews, with sufficient scores given to pragmatic factors. Internally, the series exhibited proficiency in its linguistic components due to the use of authentic language, though some teachers reported issues with the provided grammatical content. The textbook’s language capabilities received a fair rating, and the “practices and ventures” domain exhibited strong positive feedback. The cultural elements, while deemed favorable, were recommended to be depicted more realistically. Overall evaluation insinuated that the textbook has evident usability and generalizability with opportunities for improvement in adaptability and flexibility.DiscussionKey findings suggest a need for greater interactivity and appropriate activities for differing student proficiency levels to stimulate higher cognitive skills and accommodate various learning capabilities. Consequently, this study offers significant insights into the effectiveness of the “Mega Goal” series and provides valuable information for future textbook evaluations, ultimately promoting continuous improvement in English language instruction in Saudi secondary schools.